Brill's Encyclopedia of Hinduism (Brill, 2012)
Recently relaunched in March 2019 with many improvements and new content, Brill’s Encyclopedia of Hinduism presents the latest research on all the main aspects of the Hindu traditions. Its essays are original work written by the world’s foremost scholars on Hinduism. The encyclopedia presents a balanced and even-handed view of Hinduism, recognizing the divergent perspectives and methods in the academic study of a religion that is both an ancient historical tradition and a flourishing tradition today. The encyclopedia embraces the greatest possible diversity, plurality, and heterogeneity, thus emphasizing that Hinduism encompasses a variety of regional traditions as well as a global world religion. Presenting all essays and research from the heralded printed edition, Brill’s Encyclopedia of Hinduism is now available in a fully searchable, dynamic digital format. The service will include all content from the six printed volumes.
Gesehen am 30.07.25
Keywords: Datenbank; Wörterbuch; Hinduismus